SUBMARINE PINGOES: INDICATORS OF SHALLOW GAS HYDRATES IN A POCKMARK AT NYEGGA, NORWEGIAN SEA - Hovland M.; Svensen H. (My University, 2006)
Complex pockmarks up to 300 m wide and 12 m deep are located in the Nyegga area in the Norwegian Sea. Bathymetric data and direct visual documentation and sampling with ROVs (remotely operated vehicles) have shown that these pockmarks contain abundant methane-derived authigenic carbonate rocks. Furthermore, geochemical results and the finding of seep-associated organisms, including tubeworms and bacteria shows that the pockmarks are still active fluid flow locations [Hovland, M., Svensen, H., Forsberg, C.F., Johansen, H., Fichler, C., Fosså, J.H., Jonsson, R., Rueslåtten, H., 2005. Complex pockmarks with carbonate-ridges off mid-Norway: Products of sediment degassing. Marine Geology, 218, 191-206.]. Here we report the discovery of localized pingo-like sediment mounds up to 1 m high and 4 m wide. They occur inside one of the Nyegga complex pockmarks, 'G11.' All of the seven structures we investigated have four characteristics in common. (1) They have a positive topography (rounded mounds and cones). (2) They are partly covered in bacterial mats (indicating ongoing fluid flow). (3) They are partly covered in a carpet of small, living tubeworms (polychaetes, which utilize methane). (4) They have distinct corrosion pits on their surfaces, indicating fluidization and point-source corrosion of the covering sediments (probably caused by localized sub-surface hydrate dissociation). We interpret the features as true submarine pingoes, formed by the local accumulation of hydrate (ice) below the sediment surface. It is inferred that the pingoes are formed as documented hydrocarbon gases, methane, ethane, propane, and butane migrate upwards through distinctive sub-surface channels or conduits inside the pockmark. We suggest that these submarine hydrate-pingoes manifest the exact locations where fluid flow through the seafloor is currently active, and that they can therefore be used as small-scale indicators of active seepage. © 2006 Elsevier B.V. All rights reserved.
Keywords: COMPLEX POCKMARK; FLUID FLOW; GAS HYDRATES; HYDRATE PINGO; METHANE FLOW; NYEGGA; POREWATER FLOW; SEDIMENT STABILITY; SHALLOW GAS